2013
DOI: 10.1186/1471-2458-13-156
|View full text |Cite
|
Sign up to set email alerts
|

Change of urinary fluoride and bone metabolism indicators in the endemic fluorosis areas of southern china after supplying low fluoride public water

Abstract: BackgroundFew studies have evaluated health impacts, especially biomarker changes, following implementation of a new environmental policy. This study examined changes in water fluoride, urinary fluoride (UF), and bone metabolism indicators in children after supplying low fluoride public water in endemic fluorosis areas of Southern China. We also assessed the relationship between UF and serum osteocalcin (BGP), calcitonin (CT), alkaline phosphatase (ALP), and bone mineral density to identify the most sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…Our data also indicates that tea consumption by infants will result in excessive intake of fluoride which is associated with a high risk of dental fluorosis. Recently, Chen et al provided a biological dose-exposure response relationship for fluoride exposure and bone metabolism indicators and demonstrated that when urinary fluoride levels increased above 0.3 mg/L, the percentage of children with abnormal bone metabolism increased significantly [ 127 ]. Székely et al examined urinary fluoride excretion after tea consumption in young adults residing in a community with a fluoride level in drinking water of 0.1 mg/L and determined that the consumption of 200 mL of tea per day with a fluoride content of 0.42 mg increased 24 h urinary fluoride levels from 0.297 mg/L to 0.451 mg/L [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicates that tea consumption by infants will result in excessive intake of fluoride which is associated with a high risk of dental fluorosis. Recently, Chen et al provided a biological dose-exposure response relationship for fluoride exposure and bone metabolism indicators and demonstrated that when urinary fluoride levels increased above 0.3 mg/L, the percentage of children with abnormal bone metabolism increased significantly [ 127 ]. Székely et al examined urinary fluoride excretion after tea consumption in young adults residing in a community with a fluoride level in drinking water of 0.1 mg/L and determined that the consumption of 200 mL of tea per day with a fluoride content of 0.42 mg increased 24 h urinary fluoride levels from 0.297 mg/L to 0.451 mg/L [ 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALP and BGP have been recognized as early and important indicators in the evaluation of bone formation . Therefore, ALP activity and BGP content in the human osteoblasts were determined.…”
Section: Resultsmentioning
confidence: 99%
“…[151]. A large body of evidence from epidemiological studies has demonstrated that F is a potent inducer of CT expression in humans [152,153,154,155,156,157]. Of fundamental importance is the research by Chen and associates in providing a biological dose-exposure response relationship for F exposure on CT expression at relatively low intakes.…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%
“…Of fundamental importance is the research by Chen and associates in providing a biological dose-exposure response relationship for F exposure on CT expression at relatively low intakes. Notably, in this study, it was demonstrated that differential expression of CT occurs when urinary F levels exceeded 0.38 mg/L [155].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%